The Roles of Base Modifications in Kidney Cancer - Feng, Chunyue; Huang, Xiaoli; Li, Xuekun; Mao, Jianhua (Frontiers in Oncology, 2020)
Epigenetic modifications including histone modifications and DNA and RNA modifications are involved in multiple biological processes and human diseases. One disease, kidney cancer, includes a common type of tumor, accounts for about 2% of all cancers, and usually has poor prognosis. The molecular mechanisms and therapeutic strategy of kidney cancer are still under intensive study. Understanding the roles of epigenetic modifications and underlying mechanisms in kidney cancer is critical to its diagnosis and clinical therapy. Recently, the function of DNA and RNA modifications has been uncovered in kidney tumor. In the present review, we summarize recent findings about the roles of epigenetic modifications (particularly DNA and RNA modifications) in the incidence, progression, and metastasis of kidney cancer, especially the renal cell carcinomas.